1983
DOI: 10.1126/science.6301006
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Pseudoplatelets: Their Discrimination by Myeloperoxidase Demonstration

Abstract: Neutrophils, especially in acute infection or the myeloid leukemias, may shed platelet-sized particles that can readily be distinguished from true platelets because they contain neutrophil myeloperoxidase. This enzyme, unlike platelet peroxidase, is not inhibited by glutaraldehyde. The myeloperoxidase and acid hydrolase levels and continuous plasma membranes of these cell-like particles suggest that they are functional cellular entities. They further differ from platelets in that they contain nuclear remnants,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…Our data provide a mechanism whereby neutrophils can indirectly contribute to killing of mycobacteria, by the ability of infected macrophages to acquire the contents of neutrophil granules and their antimicrobial molecules. These findings are consistent with the observation that neutrophils shed "pseudoplatelets" or "cell-like" particles, containing myeloperoxidase and nuclear debris, and that these particles can be ingested by macrophages (34). It is likely that these cell-like particles are apoptotic bodies that in addition to myeloperoxidase (38), contain lactoferrin (10) and other antimicrobial peptides.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our data provide a mechanism whereby neutrophils can indirectly contribute to killing of mycobacteria, by the ability of infected macrophages to acquire the contents of neutrophil granules and their antimicrobial molecules. These findings are consistent with the observation that neutrophils shed "pseudoplatelets" or "cell-like" particles, containing myeloperoxidase and nuclear debris, and that these particles can be ingested by macrophages (34). It is likely that these cell-like particles are apoptotic bodies that in addition to myeloperoxidase (38), contain lactoferrin (10) and other antimicrobial peptides.…”
Section: Discussionsupporting
confidence: 83%
“…Depletion of neutrophils before infection enhanced mycobacterial growth in the lungs of infected animals, whereas treatment locally with MIP-2 enhanced neutrophil recruitment and decreased mycobacterial growth (14,16). Multiple functional roles for neutrophils in the host response to mycobacteria have been suggested, including the release of chemokines (17,18), the induction of granuloma formation (18), and macrophage uptake of neutrophil-specific factors such as myeloperoxidase (34) and lactoferrin (10). Bacilli can be found in human lung neutrophils (35), but whether the neutrophils contribute directly to killing remains unclear (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that in only two pathological conditions, leukaemias and acute infections, are small platelet-sized cytoplasmic fragments, not originating from megakaryocytes, observed in blood 8 9. The main explanation for this phenomenon is that leukaemic cells have the tendency to fragment and disrupt 8.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that in only two pathological conditions, leukaemias and acute infections, are small platelet-sized cytoplasmic fragments, not originating from megakaryocytes, observed in blood 8 9. The main explanation for this phenomenon is that leukaemic cells have the tendency to fragment and disrupt 8. However, further investigations in leukaemias have clearly indicated that pseudoplatelets originate from the cells of granulocyte line, monocytes and lymphoblasts by budding of their peripheral cytoplasm 8…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation